2020
DOI: 10.1177/1069397120915454
|View full text |Cite
|
Sign up to set email alerts
|

Gender Role Attitudes in the International Social Survey Programme: Cross-National Comparability and Relationships to Cultural Values

Abstract: Differences in societal views on the roles of men and women have been addressed in many large-scale comparative studies by employing indicators of gender roles attitudes from cross-sectional surveys. Assuming that cross-country differences in gender role attitudes are linked to the prevailing cultural value orientations in each society, this study aims at investigating the association between societal views on gender roles, as measured by the International Social Survey Programme (ISSP), and the prevailing cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 87 publications
(141 reference statements)
0
17
0
Order By: Relevance
“…The alignment optimization, which is also applicable in the Bayesian framework, has been proposed as a convenient alternative to MGCFA (Asparouhov and Muthén, 2014;Kline, 2015). Its application in real-data studies (Flake and McCoach, 2018;Lomazzi, 2018;Lomazzi and Seddig, 2020) demonstrated that it is a promising technique for scholars who aim to adopt approximate equivalence while retaining the frequentist approach.…”
Section: Approaches To Measurement Equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…The alignment optimization, which is also applicable in the Bayesian framework, has been proposed as a convenient alternative to MGCFA (Asparouhov and Muthén, 2014;Kline, 2015). Its application in real-data studies (Flake and McCoach, 2018;Lomazzi, 2018;Lomazzi and Seddig, 2020) demonstrated that it is a promising technique for scholars who aim to adopt approximate equivalence while retaining the frequentist approach.…”
Section: Approaches To Measurement Equivalencementioning
confidence: 99%
“…Regarding the approximate approach to equivalence, the alignment method was used to assess invariance of the same first-order factor model across the same group of countries. Following previous studies in which the variance between groups was large (Asparouhov and Muthén, 2014;Lomazzi and Seddig, 2020), the study applied FIXED alignment, employed ML and MLR estimations, and compared the results. Furthermore, if the amount of non-invariant parameters exceeded 25%, a Monte Carlo investigation was carried out to confirm the alignment results (Asparouhov and Muthén, 2014).…”
Section: Analytical Strategymentioning
confidence: 99%
“…The Triangle Theory of Violence (Galtung, 2016) indicates that offering different life opportunities according to sex facilitates discriminatory attitudes. Indeed, Lomazzi and Seddig (2020) conducted a cross-cultural study in which they found that 568 Beatriz Pérez Sánchez et al anales de psicología / annals of psychology, 2021, vol. 37, nº 3 (october) countries with more progressive gender attitudes also presented more egalitarian social values.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of value analysis, mass surveys of people from different countries deserve attention [4,[7][8][9][10]. Ronald Inglehart and Wayne E. Baker used data from 3 waves of value surveys around the world found evidence of significant changes in some and the preservation of other cultural traditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers show how the behavior of people in countries with different value systems differs. For example, traditional gender roles are manifested in societies with a focus on hierarchy and affiliation, while progressive views are more pronounced in egalitarian societies [8]. It was found that society's commitment to autonomy and hierarchy is associated with a higher level of conflict between family and work [4].…”
Section: Introductionmentioning
confidence: 99%